PENGUKURAN KINERJA MESIN PRODUKSI MENGGUNAKAN METODE OVERALL THROUGHPUT EFFECTIVENESS GUNA MENINGKATKAN HASIL PRODUKSI DI PT XYZ - Sigit Wahono; Tedjo Sukmono (Spektrum Industri, 2017)
PT XYZ is one manufacturing company engaged in the production of animal feed. In the production process sometimes product results does not comply with the requests received by the company. There are many factors which could this problem happened. One of them is less than the maximum engine performance production caused by high downtime on a production machine. To find out how well the performance of a production machine, then it is held a performance assessment by using Overall Throughput Effectiveness (OTE) method.Overall Throughput Effectiveness calculations performed on the line pellet machine was obtained 48.97%. This value is still far to the standard value desired by the company which is 70%. For performance improvement can be done by improving the engine damaged and analyzed by using Failure Mode and Effect Analysis (FMEA). From the analysis showed that the failure modes of root dies breaking up with the value of the RPN 224 is a damage that must be repaired immediately because obtaining the highest RPN value compared to other failure modes.Keywords: Measurement of engine performance, OEE, OTE, FMEA